A Class of Distal Functions on Semitopological Semigroups - Jabbari, A.; Vishki, H.R.E. (Інститут математики НАН України, 2009)
The norm closure of the algebra generated by the set {n→λ^nk : λ belongs T and k belongs N} of functions on (Z,+) was studied in [11] (and was named as the Weyl algebra). In this paper, by a fruitful result of Namioka, this algebra is generalized for a general semitopological semigroup and, among other things, it is shown that the elements of the involved algebra are distal. In particular, we examine this algebra for (Z,+) and (more generally) for the discrete (additive) group of any countable ring. Finally, our results are treated for a bicyclic semigroup.